Transferrin-Targeted Polymeric Micelles Co-Loaded with Curcumin and Paclitaxel: Efficient Killing of Paclitaxel-Resistant Cancer Cells - Abouzeid, Abraham H. (2014)
PURPOSE: The ability to successfully treat advanced forms of cancer remains a challenge due to chemotherapy resistance. Numerous studies indicate that NF-κB, a protein complex that controls the expression of numerous genes, as being a key factor in producing chemo-resistant tumors. In this study, the therapeutic potential of transferrin (TF)-targeted mixed micelles, made of PEG-PE and vitamin E co-loaded with curcumin (CUR), a potent NF-κB inhibitor, and paclitaxel (PCL), was examined. METHODS: The cytotoxicity of non-targeted and TF-targeted CUR and PCL micelles as a single agent or in combination was investigated against SK-OV-3 human ovarian adenocarcinoma along with its multi-drug resistant (MDR) version SK-OV-3-PCL-resistant (SK-OV-3TR) cells in vitro. RESULTS: Our results indicated that the TF-targeted combination micelles were able to improve the net cytotoxic effect of CUR and PCL to clear synergistic one against the SK-OV-3 cells. In addition, even though the non-targeted combination treatment demonstrated a synergistic effect against the SK-OV-3TR cells, the addition of the TF-targeting moiety significantly increased this cytotoxic effect. While keeping CUR constant at 5 and 10 μM and varying the PCL concentration, the PCL IC(50) decreased from ~ 1.78 and 0.68 μM for the non-targeted formulations to ~ 0.74 and 0.1 μM for the TF-targeted ones, respectively. CONCLUSION: Our results indicate that such co-loaded targeted mixed micelles could have significant clinical advantages for the treatment of resistant ovarian cancer and provide a clear rational for further in vivo investigation.